Mudar de alimentação para mudar o mundo - Joana Fernandes (e-cadernos ces, 2021)
In this text, the author defends the role of an eco-solidary, vegan, organic and local cuisine in the organisation of different events, taking as example her participation in the organisation of the Fourth International Ecosocialist Encounters. The NGO Associação Caldeira Negra – which the author co-founded according to the principles of regional food sovereignty and which was responsible for feeding hundreds of people during this event – chooses to cook vegan, local and organic food as a tool to fight for a less polluting and more solidary world, as well as a fair, healthy agriculture for all beings (including humans); it also fights for a nutrition based on products from an agriculture that sustains those who produce avoiding animal suffering or excessive stress for the environment.